STRATEGI MANAJEMEN HUMAS DALAM MENINGKATKAN CITRA MADRASAH DI MTs AL MAARIF 01 SINGOSARI MALANG - Choirotul Maulidiyah (STAI Ma'had Aly Al-Hikam Malang, 2020)
This study originated from the author's observations on the phenomenon of change in MTs Al Maarif 01, which was originally founded in 1923 AD, the Madrasah which was named Misbachul Wathon which continued to develop with demands for rules and regulations, so on July 1 1959 AD it changed to Madrasah Stanawiyah. Nahdlotul Ulama and continues to grow until now to become MTs Al Maarif 01 Singosari Malang. Based on this phenomenon, the writer intends to reveal the public relations strategy in enhancing the image of Madrasah Tsanawiyah Al Maarif Singosari Malang with sub focus: Public Relations Management Strategies in improving the image of Madrasah Tsanawiyah Al Maarif 01 Singosari, supporting and inhibiting factors in improving the image of MTs Al Maarif 01 Singosari.This research uses qualitative research with the type of case study research. Data collection techniques using interviews, observation, and documentation. While the data analysis technique, researchers used three interconnected components, namely data reduction, data presentation, and drawing conclusions. To obtain objective data, it is done checking the validity of the data by making continuous observations, triggering data sources, methods and theories, checking members, checking the adequacy of references.The results of the research that have been carried out show that: 1) public relations strategies in improving the image of Madrasah Tsanawiyah Al Maarif 01 Singosari, namely public relations working with all members in madrasas such as the principal, Deputy Curriculum, Student Assistant and other teachers and staff, and also have a work program. 2) supporting and inhibiting factors in improving Madrasah Image: supporting factors a. Big names of foundations and madrasah founders (the NU scholars in 1957) b. Fulfillment of facilities and infrastructure c. trusted by related agencies and trusted by the community d. good cooperation from all Madrasah, Pesantren and student guardians e. Assignment of assignments by the foundation in accordance with the experts. Inhibiting factors, namely: a. There are activities that coincide with the pesantren b. Home visit is not smooth because the guardian is far away (outside the city, outside the island) and limited time c. There are limited funds.